High-level production of l-homoserine using a non-induced, non-auxotrophic Escherichia coli chassis through metabolic engineering. (May 2021) - Zhang, Yu; Wei, Minhua; Zhao, Guihong; Zhang, Wenjie; Li, Yingzi; Lin, Beibei; Li, Yanjun; Xu, Qingyang; Chen, Ning; Zhang, Chenglin
Graphical abstract: Highlights: A non-induced and non-auxotrophic E. coli for homoserine synthesis was obtained. Degradation of homoserine was dynamically attenuated rather than blocked. Efflux of homoserine was precisely modulated by promoter optimization. Abstract: l -Homoserine is a valuable non-proteinogenic amino acid used in the synthesis of various important compounds. Microbial fermentation has potential value for producing l -homoserine on a large scale, but suffers from a low yield and the need for expensive additives. In this study, a non-induced, non-auxotrophic, plasmid-free Escherichia coli chassis for the high-efficiency production of l -homoserine was constructed. Initially, the l -homoserine degradation pathway was dynamically attenuated. Subsequently, systems metabolic engineering strategies were employed, including reinforcing the synthetic flux, improving NADPH generation, and elevating l -homoserine efflux. The constructed strain HOM-14, produced 60.1 g/L l -homoserine without additional supplements or inducers, which achieved the highest fermentative production efficiency of l -homoserine till date. Moreover, common byproducts, such as acetate, did not accumulate. The strategies presented here can be applied in the further engineering of chassis for the scale-up production of l -homoserine and derivatives.